Karakteristik dan Hubungan Pengetahuan Serta Tindakan Stimulasi dengan Perkembangan pada Anak Usia Toddler - Misniarti Misniarti; Sri Haryani (Journal of Telenursing (JOTING), 2025)
This study aims to determine the characteristics and relationship of knowledge and stimulation actions with the development of toddler-aged children in the working area of ​​the Perumnas Health Center. The method used is a descriptive analytical design with a cross-sectional approach. The results showed that 72 (72%) were aged > 25 years and 82 (82%) had secondary education and almost all respondents were unemployed 68 people (68%). There is a significant relationship between maternal knowledge and child development, and maternal stimulation actions are related to child development. The conclusion is that most respondents were aged > 25 years and some had secondary education and more than half of respondents were unemployed. Between maternal knowledge and stimulation there is a significant relationship with the development of toddler-aged children.   Keywords: Development, Stimulation, Toddler